Art as Literacy - Albers, Peggy (Language Arts Language Arts, 1997)
Challenges educators to consider the meaning-making potential of art. Explores how this was done in a middle school art classroom by examining the role of the teacher, students' enculturation in art, art as process, and reflection in art. Notes the risks involved when students sometimes create visual meanings that are racist, homophobic, or sexist. (SR)
Keywords: éducation; enseignement; enseignement des arts; enseignement secondaire; literacy; middle schools